Continental carbonate facies of a Neoproterozoic panglaciation, north‐east Svalbard. Issue 2 (4th February 2016) - Fairchild, Ian J.; Fleming, Edward J.; Bao, Huiming; Benn, Douglas I.; Boomer, Ian; Dublyansky, Yuri V.; Halverson, Galen P.; Hambrey, Michael J.; Hendy, Chris; McMillan, Emily A.; Spötl, Christoph; Stevenson, Carl T. E.; et al.
Abstract: The Marinoan panglaciation ( ca 650 to 635 Ma) is represented in north‐east Svalbard by the 130 to 175 m thick Wilsonbreen Formation which contains syn‐glacial carbonates in its upper 100 m. These sediments are now known to have been deposited under a CO2 ‐rich atmosphere, late in the glaciation, and global climate models facilitate testing of proposed analogues. Precipitated carbonates occur in four of the seven facies associations identified: Fluvial Channel (including stromatolitic and intraclastic limestones in ephemeral stream deposits); Dolomitic Floodplain (dolomite‐cemented sand and siltstones, and microbial dolomites); Calcareous Lake Margin (intraclastic dolomite and wave‐rippled or aeolian siliciclastic facies); and Calcareous Lake (slump‐folded and locally re‐sedimented rhythmic/stromatolitic limestones and dolomites associated with ice‐rafted sediment). There is no strong cyclicity, and modern analogues suggest that sudden changes in lake level may exert a strong control on facies geometry. Both calcite and dolomite in stromatolites and rhythmites display either primary or early diagenetic replacive growth. Oxygen isotope values (−12 to +15‰VPDB ) broadly covary with δ 13 C. High δ 13 C values of +3·5 to +4·5‰ correspond to equilibration with an atmosphere dominated by volcanically degassed CO2 with δ 13 C of −6 to −7‰. Limestones have consistently negative δ 18 O values, while rhythmic and playa dolomites preserve intermediate compositions, and dolocretes possess slightly negative to strongly positive δ 18 O signatures, reflecting significant evaporation under hyperarid conditions. Inferred meltwater compositions (−8 to −15·5‰) could reflect smaller Rayleigh fractionation related to more limited cooling than in modern polar regions. A common pseudomorph morphology is interpreted as a replacement of ikaite (CaCO3 ·H2 O), which may also have been the precursor for widespread replacive calcite mosaics. Local dolomitization of lacustrine facies is interpreted to reflect microenvironments with fluctuating redox conditions. Although differing in (palaeo)latitude and carbonate abundance, the Wilsonbreen carbonates provide strong parallels with the McMurdo Dry Valleys of Antarctica.